2023
DOI: 10.1021/acsbiomedchemau.2c00089
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Copper Nanobiomaterials with Antimicrobial Properties

Abstract: In this work, nanostructured copper materials have been designed, synthetized, and evaluated in order to produce a more efficient and sustainable copper bionanohybrid with catalytical and antimicrobial properties. Thus, conditions are sought where the most critical steps are reduced or minimized, such as the use of reducing agents or the cryogenization step. In addition, the new materials have been characterized through different techniques, and their oxidative and reductive capacities, as well as their antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In addition, the use of a protein allows for the control of the size and shape of the metal nanoparticles produced, as well as the ability to produce them in a monodisperse way (Figure 2). However, a recent study conducted by our group also demonstrated the effect of include a reduction step in the synthesis process of nanobiohybrids, where depending on However, a recent study conducted by our group also demonstrated the effect of include a reduction step in the synthesis process of nanobiohybrids, where depending on the amount of reducing agent added, changes in metal structure are achieved as well as different antimicrobial efficiencies [48]. In the synthesis method, copper sulphate as the metal salt, lipase from Candida antarctica (CAL-B) as the scaffold enzyme, and sodium borohydride as the reducing agent were used.…”
Section: Synthesis Of Metal Nanoparticles (Ag Cu Zn Ce)mentioning
confidence: 81%
See 2 more Smart Citations
“…In addition, the use of a protein allows for the control of the size and shape of the metal nanoparticles produced, as well as the ability to produce them in a monodisperse way (Figure 2). However, a recent study conducted by our group also demonstrated the effect of include a reduction step in the synthesis process of nanobiohybrids, where depending on However, a recent study conducted by our group also demonstrated the effect of include a reduction step in the synthesis process of nanobiohybrids, where depending on the amount of reducing agent added, changes in metal structure are achieved as well as different antimicrobial efficiencies [48]. In the synthesis method, copper sulphate as the metal salt, lipase from Candida antarctica (CAL-B) as the scaffold enzyme, and sodium borohydride as the reducing agent were used.…”
Section: Synthesis Of Metal Nanoparticles (Ag Cu Zn Ce)mentioning
confidence: 81%
“…In addition, an increase in the reducing agent generated larger and agglomerated nanobiohybrids (Figure 3). the amount of reducing agent added, changes in metal structure are achieved as well as different antimicrobial efficiencies [48]. In the synthesis method, copper sulphate as the metal salt, lipase from Candida antarctica (CAL-B) as the scaffold enzyme, and sodium borohydride as the reducing agent were used.…”
Section: Synthesis Of Metal Nanoparticles (Ag Cu Zn Ce)mentioning
confidence: 99%
See 1 more Smart Citation
“…This redox activity can potentially damage bacteria and generate highly reactive hydroxyl radicals and other reactive oxygen species. 64,65 These radicals can cause detrimental reactions, including destabilization of the cell wall and oxidation of proteins and lipids, thereby contributing to the antibacterial effect. 66 Furthermore, copper ions can disrupt bacterial cell function by replacing and/or binding with native cofactors in metalloproteins.…”
Section: Resultsmentioning
confidence: 99%
“…[21] This technology has been successfully applied until now in different areas, bioremediation of organic pollutants, [24] fine chemistry [20,23,25] or even as novel antiviral and antimicrobial material formation. [26][27] Some of these results are the most relevant in the literature in the particular catalytic process, demonstrating the advantages to use nanotechnology vs bulk materials, besides the simple synthetic approach of them. The conservation of both activities, producing bifunctional (enzyme and metal) catalysts have been recently successfully used in complex chemical routes by cascade processes in very sustainable conditions, [28][29][30][31][32][33][34][35][36] and some of them will be discussed in this article (Figure 1).…”
Section: Introductionmentioning
confidence: 92%